2011
DOI: 10.1111/j.1463-6395.2010.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and lipid chemistry of specialized epidermal structure of Indian porcupines and hedgehog

Abstract: Poddar-Sarkar, M., Raha, P., Bhar, R., Chakraborty, A. and Brahmachary, R.L. 2011. Ultrastructure and lipid chemistry of specialized epidermal structure of Indian porcupines and hedgehog. -Acta Zoologica (Stockholm) 92: 134-140.In the present study, we investigated the ultrastructural variations of specialized epidermal structure of Indian porcupines (Hystrix indica and Atherurus macrourus) and hedgehog (Hemiechinus collaris) as well as the variation in the fatty acid composition of total lipid fraction. Scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The tongue of the domestic cat, the subject of the current study, appeared as an elongated organ located at the lower jaw. On the ventral surface of the tongue, there is an elongated lingual membranous fold that makes the tongue touch the floor of the oral cavity and thus resembles most mammals [7], [8]. The results found that the tongue of the domestic cat is composed of three regions: the rounded apex, a broad lingual body, and a lingual root; this result is in agreement with previous studies [9], [10].…”
Section: Discussionsupporting
confidence: 91%
“…The tongue of the domestic cat, the subject of the current study, appeared as an elongated organ located at the lower jaw. On the ventral surface of the tongue, there is an elongated lingual membranous fold that makes the tongue touch the floor of the oral cavity and thus resembles most mammals [7], [8]. The results found that the tongue of the domestic cat is composed of three regions: the rounded apex, a broad lingual body, and a lingual root; this result is in agreement with previous studies [9], [10].…”
Section: Discussionsupporting
confidence: 91%
“…Cortical layers are thin in spikes (Poddar‐Sarkar et al . ), stiletto‐like spines (Fig. A) and bristle‐like spines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…; Poddar‐Sarkar et al . , ; Church et al . ), the scale orientation and scale margin were unique in appearance in this genus.…”
Section: Discussionmentioning
confidence: 99%
“…It is smaller and quicker than the West European hedgehog, weighing just 250–400 g and when a predator approaches, it either balls up or attempts to evade them using its relatively short needles (Qumsiyeh, 1996). Although it primarily eats insects, this hedgehog can also consume small animals and plants (Poddar‐Sarkar et al., 2011). Many macro‐anatomical studies on the skeletons of small wild mammals, including mole rats (Ozkan, 2007), wombats (Saber, 2013), rabbits (Ajayi et al., 2012), porcupines (Yilmaz et al., 1998), African giant rats (Olude et al., 2010) and few hedgehog subspecies such as giant hedgehogs (Villier & Carnevale, 2013) and Indian hedgehogs (Kumar et al., 2020), have been reported.…”
Section: Introductionmentioning
confidence: 99%